Digital Escapes: The Role of Gadgets in Supporting Student Mental Health Amid Academic Pressures - Carolina Retmawati Putri (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
In recent years, stress and anxiety among young people, particularly students, have significantly increased. Academic pressures, assignment demands, class participation, and personal issues such as relationships, finances, and family problems exacerbate this situation. These stressors often negatively impact students' mental and physical health, leading to sleep disturbances, digestive problems, and a weakened immune system. To cope with these pressures, students frequently turn to gadgets and digital applications as tools for managing stress and maintaining emotional balance. This study aims to explore the impact of stress and anxiety on student’s mental and physical health, and how technology use can serve as an effective coping strategy. The research uses surveys and interviews to gather data from students on their stress and anxiety levels, and how they use gadgets to mitigate the negative effects of stress on their well-being. The study analyses how students use technology through gadgets to access various applications such as music, movies, podcasts, games, social media, and online dating apps as part of their coping strategies. Findings suggest that the judicious use of technology can help students manage stress and anxiety, reduce its negative effects on mental and physical health, and improve their overall well-being. However, the study also emphasizes the importance of awareness about the negative impact of excessive technology use. This research aims to provide insights into how students can use technology to reduce stress and anxiety's impact on their health.